2020
DOI: 10.1111/1467-8268.12440
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth dynamics between resource‐rich and resource‐poor countries in sub‐Saharan Africa: The role of politics and institutions

Abstract: This paper employs the system generalized method of moments to examine the diversity of economic growth in 33 resource-rich and resource-poor countries in sub-Saharan Africa (SSA) over the period 1996-2017. The last decade has witnessed resource-poor countries such as Rwanda and Ethiopia sustain impressive economic growth while resource-rich countries such as Nigeria and the Democratic Republic of the Congo continue to struggle. On the other hand, non-oil resource-rich countries such as Botswana and Namibia re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
3
18
0
2
Order By: Relevance
“…As a follow up to the Report of Coleman et al (1966) on public school funding advocacies, Jackson et al ( 2016) investigated the effects of school spending on educational outcomes in the United States and found that the governance element (such as school finance reforms), moderated the link between school spending and educational outcomes in the country. This finding corroborates the notion in the governance literature (Adika, 2020;Ogbeide & Adeboje, 2020), that strong institutions and governance improve economic outcomes such as economic growth and business entrance in African countries.…”
Section: Theoretical Anchor and Empirical Evidencesupporting
confidence: 90%
“…As a follow up to the Report of Coleman et al (1966) on public school funding advocacies, Jackson et al ( 2016) investigated the effects of school spending on educational outcomes in the United States and found that the governance element (such as school finance reforms), moderated the link between school spending and educational outcomes in the country. This finding corroborates the notion in the governance literature (Adika, 2020;Ogbeide & Adeboje, 2020), that strong institutions and governance improve economic outcomes such as economic growth and business entrance in African countries.…”
Section: Theoretical Anchor and Empirical Evidencesupporting
confidence: 90%
“…These results on challenges with ability to feed among many Nigerians in the face of the country's 'resource-rich' status has been taunted as attributable to a 'resource curse phenomenon', however there is weak evidence for this (Adika, 2020). An explanation for the challenges could be found in Bakaliset al (2020)'s study clarifying that the two-faced nature of COVID-19 on food security as being through direct (disrupted international food supply and demand systems) and indirect (by undermined economic access to food through degrading the purchasing power of the population).…”
Section: Discussionmentioning
confidence: 99%
“…Nigeria is among one of the major supplies of crude oil in the international market. However, the country has been hit hard in the global oil market due to the uncertainty of the global oil prices (Adika, 2020; Ding et al, 2020). Therefore, in its efforts to diversify its economy, Nigeria have intensified efforts to shift away from over-reliance on crude oil and its commodities by investing in agriculture production and exports (MBNP, 2017).…”
Section: Introductionmentioning
confidence: 99%